Experimental thermal and electrical performances of a PVT-air collector coupled to a humidification-dehumidification (HDH) cycle - Ahmed Ghazy (International Journal of Renewable Energy Development, 2023)
Despite their low electrical efficiencies, PVs are widely used to generate electricity from abundant solar energy. In order to maximize the utilization of incident solar energy, PVT collectors have been used to simultaneously generate electricity and thermal energy. Furthermore, combining PVTs with humidification-dehumidification (HDH) cycles can provide electricity and potable water in remote, arid rural areas that are not connected to the grid. In this paper, a PVT-air collector was coupled to an air-heated closed HDH cycle. Air was heated within the PVT collector and humidified by saline water spray inside the humidifier. Fresh water was produced by cooling humid air inside a dehumidifier that is cooled by saline water. The thermal and electrical performances of the PVT-HDH system were experimentally studied and compared to the electrical performance of a PV module with similar characteristics. The results demonstrated a significant decrease in PV temperature within the PVT-HDH system, which resulted in a 20% increase in the output power of the PVT-HDH system at midday compared to the identical PV module. In addition, the PVT-HDH system produced about 3.8 liters of water distillate for a PV module surface area of 1.48 m × 0.68 m, which contributed about 38% to the overall efficiency of the PVT-HDH system.